Bolehkah Gereja-Gereja Kristen Tetap Terpisah? - George Ludwig Kirchberger (Jurnal Ledalero, 2016)
The author starts from the clear statement of the Second Vatican Council,“that the Church is a single flock, there are not many Churches. God established a single Church by sending His Son and the Spirit”. Today, the “separated” Churches”, are in real communion, although the communion is not yet complete. Through baptism all Christians, in each of the Christian Chruches, are members of the one Body of Christ. This is a strong bond and has to be taken as more resilient than any differences that may diminish unity. Therefore we must ask: what must be regarded as a difference that is significant enough to grant one the right to deem one’s Church as still separated? This article outlines the eight theses of Heinrich Fries and Karl Rahner where they show, with detalied argumentation, that today the Christian Churches can come together in communion. The article draws to the conclusion that the Christian Church has a moral obligation to live in a communion that is already possible, and has no right to state that the Churches can remain separated from each other. Keywords: Reformation, church unity, separated church ------------------------------------------------------------------------------------------------------------------------- Penulis artikel ini bertolak dari penegasan Konsili Vatikan II “bahwa Gereja itu merupakan satu kawanan, tidak ada Gereja-gereja Allah dalam bentuk jamak, Allah hanya mendirikan satu Gereja melalui perutusan Putra dan Roh-Nya”. Semua Gereja yang sekarang ini masih “terpisah”, berada dalam suatu persekutuan yang sungguh riil, meskipun tidak sepenuhnya. Melalui sakramen baptis semua orang Kristen dari semua Gereja Kristen menjadi anggota pada satu tubuh Kristus. Inilah suatu ikatan yang sangat kuat dan pada dasarnya mesti dianggap lebih utama dari pelbagai perbedaan yang mengurangi persekutuan itu. Oleh karena itu mesti ditanya, apa yang bisa dianggap sebagai perbedaan yang cukup besar untuk memberikan hak, untuk tetap menyatakan diri sebagai Gereja terpisah. Sebagian besar artikel ini merupakan perkenalan terhadap delapan tesis dari Heinrich Fries dan Karl Rahner, di mana mereka memperlihatkan secara teliti dan argumentatif tesis bahwa sudah saatnya Gereja-gereja Kristen bersatu. Artikel ini menyimpulkan bahwa Gereja Kristen mempunyai kewajiban moral untuk hidup dalam persekutuan yang sudah mungkin itu dan tidak lagi mempunyai hak untuk menyatakan diri sebagai Gereja yang terpisah satu sama lain. Kata-kata kunci: Reformasi; Kesatuan Gereja; Gereja terpecah